1996
DOI: 10.1007/s002280050155
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the rate of 6-mercaptopurine methylation in the erythrocytes, liver and kidney in an Italian population

Abstract: We tested this hypothesis by measuring TPMT activity in erythrocyte preparations from adults and newborns and observed polymorphic distribution of TPMT activity in the adult and newborn erythrocytes. The activity of TPMT was higher in red cells from the newborns than adults. The frequency distribution of TPMT activity was also investigated in the liver and kidney. In the kidney, TPMT activity fell into two subgroups, whereas in the liver the distribution pattern was more complex. The activity of TPMT in erythr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…This difference may be important clinically, and from a practical standpoint it may be more appropriate to start such patients on lower doses of azathioprine (0.5 mg/kg/day) rather than the more conventional recommended dose of 1 mg/kg/day. This view is supported by the fact that significant discrepancy exists between the measured activity of TPMT enzyme in erythrocytes and liver from the same subject [26]. TPMT values of only half the cases fell within the 95% confidence limits, suggesting that the control of hepatic and/or erythrocyte TPMT is multifactorial [26].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This difference may be important clinically, and from a practical standpoint it may be more appropriate to start such patients on lower doses of azathioprine (0.5 mg/kg/day) rather than the more conventional recommended dose of 1 mg/kg/day. This view is supported by the fact that significant discrepancy exists between the measured activity of TPMT enzyme in erythrocytes and liver from the same subject [26]. TPMT values of only half the cases fell within the 95% confidence limits, suggesting that the control of hepatic and/or erythrocyte TPMT is multifactorial [26].…”
Section: Discussionmentioning
confidence: 90%
“…This view is supported by the fact that significant discrepancy exists between the measured activity of TPMT enzyme in erythrocytes and liver from the same subject [26]. TPMT values of only half the cases fell within the 95% confidence limits, suggesting that the control of hepatic and/or erythrocyte TPMT is multifactorial [26].…”
Section: Discussionmentioning
confidence: 90%
“…4 Red blood cells (RBC) are convenient cells to study the thiopurine methyltransferase polymorphism and the intracellular metabolism of mercaptopurine. RBC TPMT activity has been demonstrated to correlate with the TPMT activity measured in various cells or organs (lymphocytes, 6 lymphoblasts, 7 (kidney, 8 liver 9 ), and RBC 6-thioguanine nucleotide concentrations are proposed for the monitoring of 6-MP during maintenance of ALL. Individuals inheriting a TPMT deficiency or patients heterozygous at the TPMT locus exhibit hematological intolerance of standard doses of mercaptopurine by a mechanism involving the accumulation of thioguanine nucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…3 Several confounding factors such as treatment (by thiopurine or methotrexate) or analytical variations can affect TPMT activity measurement. 4,5 Although some articles conclude that there is a higher TPMT activity in children, Ganiere-Monteil et al, in a population of 147 children and 304 healthy adult blood donors, showed a slight, but significantly, lower TPMT activity in children than in adults (18.62 ± 4.14 vs. 19.34 ± 4.09 nmol/h/mL; P = 0.033). 6 However, this minor difference is almost certainly not clinically relevant during thiopurine therapy.…”
mentioning
confidence: 99%
“…3 Results consistent with these observations have been reported by other authors. 4,5 Moreover, a recent study showed that IBD patients 6 years of age or younger treated with thiopurines had an 85% increase in probability of response if taking a dose >3.0 mg/kg/day, that is considered the upper limit for the safe dose of this medication in the general adult population, compared to a dose of 2-3 mg/kg/ day. These data support the view that closely monitored dose escalation beyond the standard dosing range, including evaluation of thiopurine metabolites, may be effective and well tolerated 6 in very young patients.…”
mentioning
confidence: 99%